Konsep Creativity, Confident, and Friendship pada Perancangan Interior Sekolah Anak Gymboree - Chandra, Clarissa (Intra, 2013)
---- In the school building, the design of the interior space is a major concern, because an interior space is well designed and properly will be able to support the childrens learning process. Gymboree Playgroup hasÂ  several concept such as creativity, confidence and friendship. Gymboree also has a wide range of classes, such as play and learn, music classes, art classes, gymnastic classes, and educational classes. The diversity of the class at the school is what makes the school attractive to Gymboree Playgroup designed. This design aims to create a school that can spur creativity, confidence and friendship among children. Design methods used include the manufacture of critical review, proposal design, literature review, and conduct surveys, create programming, schematic and design development, and then proceed with the final design and mockups. Design results will show how to design schools that reflect Gymboree corporate identity, as well as how to support creativity, confidence and friendship in children through design.